(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The paper analyzes the so-called posthumous assisted reproduction, a practice that, despite the prohibition established by law n. 40/2004, seems to be more and more widespread in our country and raises several delicate interpretative issues related to the reconstruction of the legal status of the child from the point of view of the status filiationis and inheritance rights towards the deceased parent.